Characteristics phetoplacental complex change in women with pulmonary tuberculosis, complicated by iron deficiency anemia - Zadorozhnyi, O.; Rozhkovskaya, N.; Zadorozhnaya, O.; Tarnovska, G. (Journal of Education, Health and Sport, 2022)
87 pregnant women have been examined, 57 of them had pulmonary form of TB, complicated by IDA (main group). The control group consisted of 30 conditionally somatic-healthy patients with physiological pregnancy. Changes in the parameters of erythron, increased metabolic acidosis, development of placental dysfunction (93%), violation of hemodynamics in the utero-placental-fetal basin, and low biophysical profile of the fetus were found. The main group patients received comprehensive anti-anemic, antihypoxic, detoxificative, antioxidant and membrane-stabilizing therapy. After the pathogenetic treatment, the general condition of mother and fetus improved, e. g. the total index of biophysical profile of fetus in the pregnant women of the main group increased from (6.87 ± 0.18) points to (8.73 ± 0.12) points Women with pulmonary tuberculosis and iron-deficiency anemia require complex pathogenetic therapy, which significantly improves the erythron signs, fetal, newborn and general mother’s condition.